Creation of Online Recipe System Digitalized by Software Using PHP and MYSQL Technologies (Texas Journal of Engineering and Technology, 2023)
This article provides information on creating a software digitized online recipe system using PHP and MYSQL technologies. In the article, the problems of connecting PHP and MYSQL are considered, analyzed, and as a result, the algorithm for connecting PHP and MySQL technologies is presented. Several connection methods of PHP and MYSQL were discussed and the most efficient method was taken as the solution.